The phosphodiesterase 4 inhibitor apremilast inhibits Th1 but promotes Th17 responses induced by 6-sulfo LacNAc (slan) dendritic cells - Oehrl, Stephanie; Prakash, Hridayesh; Trenkler, Nina; Wölbing, Priscila; Kunze, Anja; Döbel, Thomas; Enk, Alexander; Schäkel, Knut (Journal of dermatological science, 2017)
Background: The phosphodiesterase 4 (PDE4) inhibitor apremilast increases cellular cAMP levels and has proven effective in the treatment of psoriasis and psoriasis arthritis. We recently described 6-sulfo LacNAc dendritic cells (slanDCs) as immature DCs in blood and as a subset of inflammatory dermal DCs in psoriasis with a pronounced capacity to produce proinflammatory cytokines and to program Th17/Th1 T cell responses. Objective: The aim of this study was to investigate possible immune regulatory effects of the PDE4 inhibitor apremilast on slanDCs. Methods: In vitro studies were performed analyzing the effects of apremilast on the proinflammatory function of slanDCs and their capacity to induce Th1/Th17-biased T cell responses. Results: Increasing cAMP levels in slanDCs by PDE4 inhibition strongly reduced production of IL-12 and TNF-α. In line with these findings, co-culture experiments with apremilast-pulsed slanDCs and allogeneic T cells either from psoriasis patients or healthy controls, revealed a significant reduction of IFN-γ production and expression of the transcription factor T-bet. In parallel, production of IL-23 and IL-1ß by slanDCs was increased and co-cultured T cells revealed a largely augmented IL-17 production and an upregulated RORyt expression. Conclusions: We here demonstrate anti-inflammatory as well as Th17-promoting effects of apremilast when studying blood precursors of human inflammatory dermal dendritic cells. In the concert of the broad anti-inflammatory effects of apremilast on keratinocytes, fibroblasts and endothelial cells, the dual effect on slan+ inflammatory dermal DCs should be taken into account and may constrain therapeutic responses.